Pengaruh Gaya Hidup, Label Halal, dan Harga Terhadap Keputusan Pembelian Pada Produk Skincare MS GLOW (Studi Kasus Mahasiswa FEB UNISMA Angkatan 2019) - Lidya Ayu Ferdyana; Nurhajati Nurhajati; Muhammad Ridwan Basalamah (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to examine and explain the Influence of Lifestyle, Halal Labeling, and Prices on Purchase Decisions for MS GLOW Skincare Products in a case study of Students of the Faculty of Economics and Business, Islamic University of Malang, Class of 2019. This study uses a quantitative approach which uses the Slovin formula because the population has it is known, seeing from the results of calculating the Slovin formula to get the results of a total sample of 90 respondents. To solve the problem in this study using SPSS in analyzing, normality test, classic assumption test, hypothesis test, multiple linear regression test and adjusted R² coefficient test. The results of this study are Lifestyle, Halal Label, Prices simultaneously influence Purchasing Decisions. Keywords: Lifestyle, Halal Label, Price, Purchase Decision